Haar wavelet method for solving stiff differential equations - Ülo Lepik (Mathematical Modelling and Analysis, 2009)
Application of the Haar wavelet approach for solving stiff differential equations is discussed. Solution of singular perturbation problems is also considered. Efficiency of the recommended method is demonstrated by means of four numerical examples, mostly taken from well‐known textbooks.